Building primary care in Japan: Literature review. (13th May 2019) - Kato, Daisuke; Ryu, Hikohaku; Matsumoto, Tomoki; Abe, Kazuhiro; Kaneko, Makoto; Ko, Mezhen; Irving, Greg; Ramsay, Robin; Kondo, Masatoshi
Abstract: Japan's health system is well known for achieving one of the world's highest life expectancy with universal health coverage. However, the country now faces challenges of a rapidly aging population and changes in patterns and burden of disease. Primary care is an important component of a well‐functioning health system. In Japan, primary care services are provided in both the community and hospital settings. The distinction between primary and secondary care may not always be clear. This review is based on the framework from the 2015 WHO publication on primary care systems in Europe. Our aim is to describe the journey of primary care in Japan, with its past, present, and future as a valuable addition to the academic English literature. We also hope that this article would inspire readers outside of Japan who might face similar issues in their respective countries.